Symbiont community diversity is more variable in corals that respond poorly to stress. (12th February 2020) - Howe‐Kerr, Lauren I.; Bachelot, Benedicte; Wright, Rachel M.; Kenkel, Carly D.; Bay, Line K.; Correa, Adrienne M. S.
Abstract: Coral reefs are declining globally as climate change and local water quality press environmental conditions beyond the physiological tolerances of holobionts—the collective of the host and its microbial symbionts. To assess the relationship between symbiont composition and holobiont stress tolerance, community diversity metrics were quantified for dinoflagellate endosymbionts (Family: Symbiodiniaceae) from eight Acropora millepora genets that thrived under or responded poorly to various stressors. These eight selected genets represent the upper and lower tails of the response distribution of 40 coral genets that were exposed to four stress treatments (and control conditions) in a 10‐day experiment. Specifically, four 'best performer' coral genets were analyzed at the end of the experiment because they survived high temperature, high p CO2, bacterial exposure, or combined stressors, whereas four 'worst performer' genets were characterized because they experienced substantial mortality under these stressors. At the end of the experiment, seven of eight coral genets mainly hosted Cladocopium symbionts, whereas the eighth genet was dominated by both Cladocopium and Durusdinium symbionts. Symbiodiniaceae alpha and beta diversity were higher in worst performing genets than in best performing genets. Symbiont communities in worst performers also differed more after stress exposure relative to their controls (based on normalized proportional differences in beta diversity), than did best performers. A generalized joint attribute model estimated the influence of host genet and treatment on Symbiodiniaceae community composition and identified strong associations among particular symbionts and host genet performance, as well as weaker associations with treatment. Although dominant symbiont physiology and function contribute to host performance, these findings emphasize the importance of symbiont community diversity and stochasticity as components of host performance. Our findings also suggest that symbiont community diversity metrics may function as indicators of resilience and have potential applications in diverse disciplines from climate change adaptation to agriculture and medicine. Abstract : We examined the relationship between dinoflagellate symbiont (Symbiodiniaceae) diversity and coral host tolerance to climate stressors. Worst performing coral genets had higher alpha and beta diversity (represented by more colorful symbiont community bars in a generalized ordination plot) under ambient conditions relative to best performing genets (less colorful bars). Worst performing genets also became more variable (dashed lines) after exposure to stress treatments, whereas best performing genets remained uniform (solid lines). Some specific symbiont types were also associated with either best or worst performing host genets. These findings indicate symbiont community diversity metrics may be indicators of holobiont resilience.